UKRAINE AND AUSTRALIA: COOPERATION AND RELATIONSIN THE CONTEXT OF WORLD POLICY - Масленик, София; Секунова, Юлия (SWorldJournal, 2021)
The article considers the primary reasons for the development of Ukrainian-Australian relations and their further impact on world politics. Political practice, of course, is now a major factor in relations, but these strong relations did not appear in the